An extended genome scan in 442 Canadian multiple sclerosis-affected sibships: a report from the Canadian Collaborative Study Group. - Dyment, D; Sadovnick, A; Willer, C; Armstrong, H; Cader, Z; Wiltshire, S; Kalman, B; Risch, N; Ebers, G (2004)
Multiple sclerosis (MS) is a complex trait with a sibling relative risk (lambda(sibs)) between 18 and 36. We report a multistage genome scan of 552 sibling pairs from 442 families, the largest MS family sample assessed for linkage. The first stage consisted of a genome scan for linkage with 498 microsatellite markers at an average spacing of 7 cM in 219 sibling pairs. The second stage involved further genotyping of markers from positive regions in an independent sample of 333 affected sibling pairs. The global distribution of allele sharing for all markers showed a shift towards greater sharing within the affected sibling pair group but not in the discordant sibling pair group. This shift indicates that the number of contributing genetic factors is likely to be moderate to large. Only markers at chromosome 6p showed significant evidence for linkage (MLOD=4.40), while other regions were only suggestive (1p, 2q, 5p, 9q, 11p, 12q, 18p, 18q and 21q) with MLODs greater than 1.0. The replication analysis involving all 552 affected sibling pairs confirmed suggestive evidence for five locations, namely, 2q27 (MLOD=2.27), 5p15 (MLOD=2.09), 18p11 (MLOD=1.68), 9q21 (MLOD=1.58) and 1p31 (MLOD=1.33). Suggestive linkage evidence for a previously reported location on chromosome 17q (MLOD=1.67) and a prior association with marker D17S789 was replicated. We showed that the overall excess allele sharing we observed for the entire sample was due to increased allele sharing within the DRB1*15 negative subgroup alone. This observation is most consistent with a model of genetic heterogeneity between HLA and other genetic loci. These findings offer guidance for future genetic studies including dense SNP linkage disequilibrium analysis.